2022
DOI: 10.3390/joitmc8030116
|View full text |Cite
|
Sign up to set email alerts
|

Human Capital and Open Innovation: Do Social Media Networking and Knowledge Sharing Matter?

Abstract: This study provides empirical evidence of the effect of human capital on innovation in young entrepreneurs’ SMEs. Furthermore, this study also examines the role of social media networking and knowledge sharing, as a mediating variable, on the effect of human capital on open innovation. The current study employs the survey method to collect data. The respondents of this study are 438 young entrepreneurs who attended incubators by universities in Central Java and Yogyakarta, Indonesia. Data analysis techniques i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…In this context, one of the strategies mentioned most frequently was the transformation of the economic model towards a more sustainable one, which not only aims for the company's continuity but is also oriented towards the advancement of the Sustainable Development Goals (SDGs) and incorporates social and environmental elements (Allal-Chérif et al 2023;Prijadi et al 2022;Grama-Vigouroux et al 2023;Espinoza-Sánchez et al 2022;Del-Aguila-Arcentales et al 2022;Naz et al 2020;Rauter et al 2019). On the other hand, strategies such as crowdsourcing, which involves seeking ideas or solutions from a large group of people, often facilitated online (Gaofeng 2019;Pohlisch 2020;Taylor and Joshi 2019;Chu et al 2019); crowdfunding, which involves raising funds for a project by collecting small contributions from many individuals (Vrontis et al 2021;Troise et al 2020); and the development of networking spaces to promote idea sharing (Bednář and Danko 2020;Prijadi et al 2022), including the use of social networks (Sánchez-García et al 2022;Latifah et al 2022;Vrontis et al 2021), have also been employed.…”
Section: Main Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, one of the strategies mentioned most frequently was the transformation of the economic model towards a more sustainable one, which not only aims for the company's continuity but is also oriented towards the advancement of the Sustainable Development Goals (SDGs) and incorporates social and environmental elements (Allal-Chérif et al 2023;Prijadi et al 2022;Grama-Vigouroux et al 2023;Espinoza-Sánchez et al 2022;Del-Aguila-Arcentales et al 2022;Naz et al 2020;Rauter et al 2019). On the other hand, strategies such as crowdsourcing, which involves seeking ideas or solutions from a large group of people, often facilitated online (Gaofeng 2019;Pohlisch 2020;Taylor and Joshi 2019;Chu et al 2019); crowdfunding, which involves raising funds for a project by collecting small contributions from many individuals (Vrontis et al 2021;Troise et al 2020); and the development of networking spaces to promote idea sharing (Bednář and Danko 2020;Prijadi et al 2022), including the use of social networks (Sánchez-García et al 2022;Latifah et al 2022;Vrontis et al 2021), have also been employed.…”
Section: Main Strategiesmentioning
confidence: 99%
“…This could involve insufficient access to diverse resources needed for international expansion. Insufficient investment in research and development (Milici et al 2023;Latifah et al 2022) can hamper collaborative innovation. Inadequate funding for research and innovation can limit the development of novel ideas.…”
Section: Benefits and Challenges Of Co-creation And Open Innovation P...mentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study has highlighted the importance of human capital for innovation performance. Several studies have demonstrated the positive effect of human capital on innovation (Latifah et al, 2022). Culture is something that members have in an organization based on shared values and norms.…”
Section: Introductionmentioning
confidence: 99%
“…Coulombe et al (2014) further estimated the contribution of human capital quality to economic development that depends on innovation. Conducting a survey of entrepreneurs, Latifah et al (2022) provided empirical evidence about the crucial role of human capital in innovation.…”
mentioning
confidence: 99%